International experience in improving the evaluation of innovative projects - A. A. Tsymbal; D. P. Rabizov; E. A. Khalimon (Вестник университета)
The article is devoted to the study of the features of innovative projects, consideration of the main approaches applied in practice in foreign countries to evaluate these projects. The following research methods have been used: review of scientific literature and company websites, analysis, systematisation, classification, generalisation, description of practices. The purpose of the article is to review some international approaches to the evaluation of the innovative projects that can be used for their analysis. As a result, data has been obtained on the practice and forms of application of quantitative and qualitative approaches to the evaluation of projects and startups as well as innovation evaluation models. Companies attatch great importance to the analysis of financial indicators, degree of technological readiness as well as social and environmental components. Based on the proposed sample, which generally characterises the main approaches to the evaluation of the innovative projects both at the start and during their implementation, the authors draw conclusions about the classification of methods for evaluation of these projects and their applicability. The obtained research results can allow managers of innovative projects and startups to evaluate them from different points, thereby reducing the risks of their implementation, in particular, for the international context. The results of the study may also be in demand by venture funds, business accelerators, technology transfer centres and other representatives of the innovation ecosystem.